The Interplay Between a Vulnerable Body and a Recalcitrant Ego in the Experience of Illness - Thomas Hidya Tjaya (Jurnal Ledalero, 2025)
Human embodiment is widely acknowledged at least cognitively but often felt existentially in the experience of illness. When falling ill, the human being experiences the body not so much as a corporeal tool for world accomplishments as part of the self that is lived. Merleau-Ponty’s phenomenology offers analysis of the experience of a lived body and has contributed to its further applications in various realms including health. The emphasis, however, has been placed on the distinction between objective body and a lived body at the expense of the meaning of the particular negative experience of the body during illness. Engaging the thoughts of Husserl and Merleau-Ponty, I argue that the experience of illness gives rise to the realization of the nature of the body not merely as a lived one, but more fundamentally as a vulnerable one. In addition to a possible worse condition, such vulnerability is experienced particularly in relation to the very foundations of the human being’s existence. Informed by Sartre’s phenomenology, I show that the experience of illness also brings to the fore part of human nature as a recalcitrant conscious ego. The interplay between a vulnerable body and an obstinate ego that refuses to give in to such fragility shows the true nature of human beings beyond their sheer duality.